2011
DOI: 10.2478/s11756-011-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

The changes in the predatory behavior of the microturbellarian Stenostomum sphagnetorum on two species of toxin-secreting ciliates of the genus Spirostomum

Abstract: It is known that the microturbellarian Stenostomum sphagnetorum, a common ciliate predator, is very sensitive against different types of toxins produced by other ciliates for chemical defense, and consequently, it is not able to capture and ingests these ciliates. In particular, when the predator tries to attack one of these toxin-secreting ciliates, it is forced to regurgitate the captured prey in response to the toxin discharged from the ciliates. In this study it is shown that after repeated attacks by S. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Fungi‐related sequences were affiliated with saprotrophic species living on particulate organic matter and fermenters. As the highest trophic level in the karstified aquifer system, metazoa related to Stenostomum feed on protists and microorganisms (Buonanno ; Buonanno et al. ) while Plectidae are preferentially bacterivorous (Bert et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi‐related sequences were affiliated with saprotrophic species living on particulate organic matter and fermenters. As the highest trophic level in the karstified aquifer system, metazoa related to Stenostomum feed on protists and microorganisms (Buonanno ; Buonanno et al. ) while Plectidae are preferentially bacterivorous (Bert et al.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitated cells were washed twice, resuspended in SMB at room temperature for 2 h, and then used in experiments. The extrusome-deficient cells obtained by this procedure were healthy as control cells (Miyake et al, 2003;Buonanno, 2011). The supernatant containing the discharge from the extrusomes (here termed as 'toxin-enriched supernatant') was used immediately or dried by vacuum centrifuge and stored at -20°C until use.…”
Section: Cell Cultures and Preparation Of Extrusomedeficient Cellsmentioning
confidence: 99%
“…In a previous study, it was observed that when the predatory microturbellarian Stenostomum sphagnetorum tries to attack a specimen of S. ambiguum it is forced to regurgitate the captured prey, suggesting that a chemical defence is adopted by the ciliate temporarily trapped in the predator's pharynx (Buonanno, 2011).…”
Section: Isolation Purification and Structural Characterisation Of Tmentioning
confidence: 99%
“…The authors show, through simulations, that one possible function of waves of contraction is to enable a synchronized discharge of toxins in response to a predator. The flows generated by a large predator itself, or by a predator's attempt to eat an individual S. ambiguum 16 , might generate an initial trigger that induces widespread toxin release by the colony into the surrounding medium. Testing this hypothesis would require targeted genetic manipulations to uncouple the flow-generation and -sensing process from the toxin-release event.…”
mentioning
confidence: 99%